Energy and macronutrient intakes in Jordan: a population study - Huda Al Hourani; Buthaina Alkhatib; Islam Al-Shami; Amin N. Olaimat; Murad Al-Holy; Narmeen Jamal Al-Awwad; Mahmoud Abughoush; Nada A. Saleh; Dima AlHalaika; Omar Alboqai; Ayoub Al-Jawaldeh (Scientific Reports, 2023)
Abstract Jordan has never conducted a nutrition survey to determine nutrient and energy intakes. The current study aimed to describe the energy and macronutrient consumed by the Jordanian population. A cross-sectional food consumption study was conducted, including a sample of Jordanians using two non-consecutive 24-h dietary recalls (24-h DR) between October 2021 and March 2022. A total of 2145 males and females aged 8 to 85 years old living in households were studied. The average of two 24-h DRs for each individual was converted into energy and nutrient intakes. After measuring weight, height, and waist circumference, the body mass index (BMI) and waist-to-height ratio (WHtR) were calculated. The percentage of under-reporters was higher in women than men (58.2% vs. 45.9%). Adults and older adult women had the highest prevalence of obesity (29.6%), while adults and older adult men had the highest prevalence of overweight (41.4%). There is a significant increase in energy intake in children, boys, and all adults, compared to the recommended calories. The mean energy percentage (E %) of total fat was 38%, exceeding the upper limit of the Acceptable Macronutrient Distribution Range (AMDR). At the same time, the mean daily dietary fiber intake fell below the recommended levels (ranging from 13.5 g in children to 19.5 g in older adults). The study population consumes more fat and less fiber than the recommended levels. Actions must be taken across all age groups to correct the deviation of energy and macronutrient intakes from the recommended dietary allowances.